Análise de sistemas de energia fotovoltaica implantados em prédios públicos localizados no município de São Paulo - Oliveira, Joyce Éllen Santos de (2021)
Contemporary society, with its constant population growth, requires a high electricity production for its operation and development. With the increase in energy consumption and environmental changes caused by these processes, it is essential that several sectors of society seek alternative, sustainable, and efficient means for the development of their activities. In this context, renewable energies generate a lower percentage of environmental pollution when compared to fossil fuels. Among renewable energy sources, the use of solar energy has grown in recent years around the world, due to the development of new technologies and mainly by the easy installation and energy capture, since the photovoltaic solar system is powered by an abundant source that has an inexhaustible incidence over the earth's surface. Large buildings, such as hospitals, schools, and administrative buildings, are considerable potential polluters, as they can cause damage to the environment due to the amount of energy they use. The present work aims to analyze the photovoltaic solar system installed in public buildings located in the city of São Paulo, focusing on the project developed and installed in the Parque Natural Municipal Fazenda do Carmo (PNMFC). As a methodology for formulating the questions of the research instrument, a bibliographic research on renewable energies focused on photovoltaic energy in public buildings was carried out in a first phase. After the construction of the platform that provided theoretical and methodological support for the research, a documentary analysis of the projects developed in the implementation of photovoltaic solar energy in the studied building was carried out, associated with semi-structured interviews with managers and those responsible for the building. The analysis of the interviews was qualitative. The results showed that, according to the interviewed, the development of sustainable buildings that generate their own energy, close to the place of consumption, is a determining factor for the economy, besides being fundamental to minimize environmental impacts. Another important factor found is that public policies on fiscal and regulatory incentives, with the goal of establishing appropriate strategies and mechanisms, are fundamental to grow the use of photovoltaic solar energy in large urban centers, as is the case in the city of São Paulo.